Ezekiel and the leaders of Israel - Duguid, Iain M. (Supplements to Vetus Testamentum,, 1994)
Ezekiel and the Leaders of Israel explores the attitudes expressed in the Book of Ezekiel towards the various different leadership groups within Judean society: the monarchy, the priests and Levites, the prophets, and the lay leadership (including zᵉqēnîm, śārîm and other ruling classes). The thesis is advanced that there is a coherent and connected attitude taken toward these leadership groups throughout the book: those singled out for the most reproach in Ezekiel's critique of the past are marginalized in his plan for the future, while those who escape blame are assigned positions of honour. It is not simply a matter of tinkering with the status of a single group in society, but rather a radical and complete restructuring, designed to avoid repetition of the sins of the past.